Dietary restraint and emotional eating among elite/international combat sport athletes - Barker, L.; Ruiz, M. C.; Nevill, A.; Cloak, R.; Lane, A. M.; Devonport, T. J. (International Journal of Sport and Exercise Psychology, 2025)
In one-on-one combat sport, weight classifications are enforced to promote fair fights and minimise injury risk. Most combat sport athletes try to fight at weight much lower than their natural weight necessitating use of weight loss strategies including restrained eating prior to competition. Previous research indicates that individuals self-reporting as high in dietary restraint also self-report a higher desire to emotionally eat, which if acted upon would compromise weight management goals. This mixed-methods exploratory study examined associations between dietary restraint and emotional eating among elite/international combat sport athletes. Nineteen elite/international competitors in Brazilian Jiu Jitsu and Mixed Martial Arts completed the emotional eating scale, a revised restraint scale, and a rapid weight loss questionnaire. A subsample of six participants then completed individual interviews to explore emotional eating, particularly during the lead-up to and post-competition. Quantitative findings via non-parametric tests found high scores in restrained eating associated with a greater urge to emotionally eat. Qualitative findings via content analysis of interview data identified three themes that helped understand this association, "emotions eliciting an urge to eat", "outcomes of emotional eating", and "resisting emotional eating". Participants described a cycle of restrained eating pre-competition followed by an increased tendency toward emotional eating post-competition, with the extent of emotional eating influenced by the degree of restrained eating required and competition outcomes.